Pengaruh Komitmen Organisasional Dan Kepuasan Kerja Terhadap Kinerja Karyawan Perusahaan Daerah Air Minum Kabupaten Majalengka - Endah Prihartini (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
In this research was conducted at the Central Perusahaan Daerah Air Minum of Majalengka Regency. The purpose of this study was to determine how the commitment, organizational and influence of job satisfaction on employee performance both partially and simultaneously. This research uses a survey method with descriptive and verification analysis. The technique of data collection done by giving a questionnaire. The population in this study is the Central Perusahaan Daerah Air Minum of Majalengka Regency with 49 respondents. Testing the research. Testing the research instrument is done by testing the validity and reliability test using a Likert scale. Data analysis tool use classic assumption test, multiple linear regression analysis, coefficient of determination analysis, t test, and F test. The result of this indicate that commitment organizational, job statisfaction and employee performance is a high category. Commitment organizational has a positive and significant effect parttially on employee performance. Job satifactions has a positive and significant effect parttially on employee performance. Job satisfaction has a positive and significant effect purely on employee performance. Organizational commitment and job satisfaction together have a positive and significant effect simultaneously on employee performance.